Effects of Peel Extract from Citrus reticulata and Hesperidin, A Citrus Flavonoid, on Macrophage Cell Line - Muthi’ Ikawati; Inna Armandari; Annisa Khumaira; Yogi Ertanto (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
The extract of Citrus reticulata has been studied for its biological activities, due to its citrus flavonoid content. The extract and its flavonoid compounds exhibit growth inhibition properties in several cancer cell lines and in vivo models. Conversely, the extract can also induce cell proliferation and angiogenesis, and shows estrogenic effects, in vitro and in vivo. Because of the contrasting effects that depend on the concentration or dosage, the precise action of the extract and its flavonoids need to be elucidated in various cell types. The objective of this study is to evaluate the effect of Citrus reticulata peel extract (Citrus extract) and hesperidin, a citrus flavonoid, on the modulation of cell proliferation in the RAW 264.7 macrophage cell line. Cell viability under Citrus extract or hesperidin treatment was assessed by using the MTT assay. The expression of interleukin-10 (IL-10), an anti-inflammatory cytokine, modulated by Citrus extract was also examined by immunostaining. Low concentrations of Citrus extract at 1 and 100 μg/mL were able to induce cell proliferation, though not significantly, as shown by cell viability of 138 and 114%, respectively. At higher concentrations of 500, 750, and 1000 μg/mL, Citrus extract decreased cell viability significantly by up to 64, 46, and 36%, respectively. Accordingly, hesperidin at low (3.1 μg/mL−61.1 μg/mL) or high (152.6 μg/mL−305.3 μg/mL) concentrations increased or reduced cell viability significantly by up to 116−136% or 10−61%, respectively. The value of the 50% inhibitory concentration (IC50) of Citrus extract was more than three times higher (756 μg/mL) than that of hesperidin (203 μg/mL = 332 μM). Additionally, 250 μg/mL of Citrus extract was able to induce IL-10 expression compared with the control. These results demonstrate that Citrus extract and hesperidin exert a biphasic effect on macrophage cells. The future development of Citrus extract as a co-chemotherapeutic, anticancer, or immunomodulatory agent should include careful consideration of its biphasic effect on each cell type.